Consanguineous Marriage in Turkish Families in Turkey and in Western Europe1. Issue 3 (September 2016) - Baykara-Krumme, Helen
The paper compares the prevalence and development of consanguineous marriages between Turkish migrants in Western Europe and stayers from the same regions of origin in Turkey. Analyses draw from three-generational family data of the 2000 Families study. Findings suggest a decline of kin marriage over generations and time in both groups, but a higher prevalence of kin marriage among migrants. Parental impact was influential, but effects of transmission were lower among migrants. Kin marriage was strongly linked with cross-border partner choice. The results support previous findings and indicate the specific effect of migration on seemingly traditional patterns of marriage.